Integrating Video Documentary Into the Classroom: A Community Assessment Assignment. Issue 2 (14th March 2016) - Levinson, Samantha G.; Caldwell, Keith; Petracchi, Helen E.; Wexler, Sandra; Engel, Rafael
ABSTRACT: Community assessment is a strategy commonly taught to social work students to identify a community's strengths and challenges. This article describes the value of using video documentary as part of a community assessment assignment. We identify the advantages of using video documentary in the assessment process and the reporting of findings. We discuss the preproduction, production, and postproduction steps necessary to produce a video documentary and illustrate how such assignments can be incorporated into a social work course. We conclude by identifying the educational benefits accrued to students.